PENGARUH INVESTASI, PENGELUARAN PEMBANGUNAN, JUMLAH TENAGA KERJA, PELATIHAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI PROVINSI BALI - Primasari, Leonny; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 5 No 6 (2021): VOL 10 NO 6, JUNI 2021 [2223 - 2660], 2021)
Being popular tourist destinations Province of Bali always strive for economic growth. Economic growth measured through gross regional domestic products. The purpose of this study is to analyze effect of development spending, the number of workers and human resources simultaneously and partially on the economic growth of Province of Bali, analyze whether human resources moderate the influence of labor through the quality of human resources on economic growth. This study uses secondary data in Province Bali on period 2011-2017, using moderation regression analysis techniques. The results showed that, 1) investment, development expenditure, number of workers and training of workers simultaneously had a significant effect on economic growth in districts / cities in Bali Province 2) investment, development expenditure, number of workers and labor interaction test partially influential positive and significant towards the economic growth of districts / cities in the Province of Bali, while the training of workers has no significant effect on the economic growth of districts / cities in the Province of Bali, 3) Test interaction between number of workers and training of workers on the economic growth of districts / cities in the Province Bali has a positive and significant effect, but training has no significant effect.   Keywords: investment, development expenditure, labor force, workforce training, and economic growth